Effectiveness of Intramammary Antibiotics, Internal Teat Sealants, or Both at Dry-Off in Dairy Cows: Clinical Mastitis and Culling Outcomes - Sharif S. Aly; Emmanuel Okello; Wagdy R. ElAshmawy; Deniece R. Williams; Randall J. Anderson; Paul Rossitto; Karen Tonooka; Kathy Glenn; Betsy Karle; Terry W. Lehenbauer (MDPI AG, 2022)
Intramammary antibiotic (AB) and internal teat sealants (TS) infusion at dry-off have been used to prevent intramammary infections (IMI) in dairy cows during the dry period and reduce the risk of mastitis during the dry period and subsequent lactation. A randomized clinal trial was completed on eight California dairy herds to estimate the effects of different dry cow therapies (AB, TS, AB + TS or None) on clinical mastitis and culling. A total of 1273 cows were randomized to one of the four treatment groups over summer and winter seasons. For each enrolled cow, microbiological testing was done on quarter milk samples collected from the first detection of clinical mastitis within the first 150 days in milk (DIM) in the subsequent lactation. Statistical analysis was done using generalized linear mixed models. There were no significant differences in the odds of clinical mastitis or culling between cows treated with AB, TS, or AB + TS compared to the controls. Dry cow therapy with AB and/or TS had no statistically significant effect on clinical mastitis and cow culling during the first 150 DIM.